2015
DOI: 10.1111/all.12704
|View full text |Cite
|
Sign up to set email alerts
|

No association between vitamin D and atopy, asthma, lung function or atopic dermatitis: a prospective study in adults

Abstract: Studies suggest that vitamin D may be involved in the pathogenesis of allergic disorders, asthma and decreased lung function. However, results are inconsistent and only few prospective studies have examined adults. The purpose of this study was to investigate the association of serum 25-hydroxy vitamin D (s25(OH)D) with atopy, atopic dermatitis (AD), asthma, wheezing and impaired lung function in a prospective study of Danish adults. A random sample of 3471 persons was examined in 2006-2008. Of these, 2308 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 20 publications
1
38
0
4
Order By: Relevance
“…While there are other studies that have not found any association between vitamin D and atopy or asthma [15]. Taking together the available literature, it is not yet possible to confirm or refute the direct role of vitamin D in the development/worsening of allergic diseases, or to assign a role to Vitamin D use in an immunological therapy setting [22].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While there are other studies that have not found any association between vitamin D and atopy or asthma [15]. Taking together the available literature, it is not yet possible to confirm or refute the direct role of vitamin D in the development/worsening of allergic diseases, or to assign a role to Vitamin D use in an immunological therapy setting [22].…”
Section: Discussionmentioning
confidence: 98%
“…The global agenda for anaphylaxis research according to the World Allergy Organization anaphylaxis guidelines also stresses the importance of research in anaphylaxis [14]. Similar work looking at the role of vitamin D in anaphylaxis, asthma and allergies has already been published from other parts of the world [15,16].…”
Section: Check For Updatesmentioning
confidence: 92%
“…The consistency of such a finding in a large number of studies [5][6][7][17][18][19][20][21][22], confirms that the low level of calcidiol in such a disease is not a coincidence, and that calcidiol deficiency has a possible role in the pathogenesis of AD. The controversy in the serum level of calcidiol in AD patients is mainly viewed among adult AD patients, where several studies showed the non-significant alteration of calcidiol levels among patient and control groups [8,9]. This raises the attention that pediatric AD patients are more prone to be worsened with depressed calcidiol level being the age group that may have an increased risk of allergen penetration through the skin, specially that most allergies are initiated in childhood [2].…”
Section: Groupmentioning
confidence: 99%
“…Concerning its relation with AD, animal studies, case reports, and randomized clinical trials have suggested the role of calcidiol, through various mechanisms including immunomodulation [4]. Furthermore, an inverse relationship between the severity of AD and calcidiol levels has been previously suggested, and studies have shown that, in individuals with AD who are deficient in calcidiol, repletion of calcidiol results in improvement and decreased severity of the disease [5][6][7]; a notion that has been denied by others [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation